2012
DOI: 10.1093/ehjci/jes130
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of intracoronary gradient-based methods by coronary computed tomography angiography for the evaluation of physiologically significant coronary artery stenoses: a validation study with fractional flow reserve

Abstract: Intracoronary attenuation-based CCTA analyses, TAG and CCO, showed moderate correlation with physiological coronary artery stenosis. The incremental value of TAG or CCO to the evaluation of haemodynamically stenosis by CCTA seemed to be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 24 publications
0
62
0
1
Order By: Relevance
“…In addition, the diagnostic performance of TAG was lower but not statistically different from that of CCTA stenosis alone (AUC: 0.63 vs. 0.73, p = 0.217) [9]. Choi also demonstrated similar results showing lower diagnostic performance of TAG than that of CCTA stenosis (AUC: 0.696 vs. 0.726) among 63 patients undergoing 64-slice CCTA [22]. These findings are in line with our results demonstrating only a modest diagnostic performance of TAG.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the diagnostic performance of TAG was lower but not statistically different from that of CCTA stenosis alone (AUC: 0.63 vs. 0.73, p = 0.217) [9]. Choi also demonstrated similar results showing lower diagnostic performance of TAG than that of CCTA stenosis (AUC: 0.696 vs. 0.726) among 63 patients undergoing 64-slice CCTA [22]. These findings are in line with our results demonstrating only a modest diagnostic performance of TAG.…”
Section: Discussionmentioning
confidence: 95%
“…TAG is a novel method developed to assess the hemodynamic significance of CAD and is calculated using a linear regression model of luminal contrast attenuations in a coronary vessel obtained by manual or semi-automated techniques [9,10,[19][20][21][22]. To date, several studies have examined the relation of TAG to invasive FFR and have shown a variety in the diagnostic accuracy of TAG in predicting lesion-specific ischemia by invasive FFR \0.80.…”
Section: Discussionmentioning
confidence: 99%
“…66 In a second study of 97 vessels in 63 patients with invasive FFR, the sensitivity, specificity, PPV, and NPV of TAG were 48%, 91%, 79%, and 71%, respectively; TAG was additive to CTA alone (c-statistic increased from 0.726-0.809, P=0.025). 67 For CCO, the corresponding values were 65%, 61%, 54%, and 71%, and it did not significantly increase the c-statistic of CTA (0.726 versus 0.784, P=0.09). Comparison of TAG with CTA and FFRCT was performed in 53 patients and 82 vessels from the DISCOVER-FLOW trial; TAG sensitivity was 38% versus 72% for CTA >70% DS and 81% for FFRCT.…”
Section: Ct Myocardial Perfusion Imagingmentioning
confidence: 84%
“…[14][15][16] TAG demonstrated the feasibility for noninvasive assessment of hemodynamically significant coronary arterial stenosis and flow. [17][18][19][20] We hypothesized that the concept of intraluminal contrast media kinetics could also be applied to totally occluded vessel supplied by collateral flow. We measured TAG of totally occluded coronary arteries and validated it with the functional extent and direction of collateral flow determined by invasive coronary angiography.…”
Section: Clinical Perspective On P 490mentioning
confidence: 99%
“…[17][18][19] In brief, cross-sectional images perpendicular to the vessel centerline were reconstructed for each major coronary artery. Luminal cross-sectional area (in mm 2 ) and radiological attenuation (in HU) were measured at 5-mm intervals from the ostium (TAG of an entire artery, TAG all ) or just distal to CTO segment (TAG of a distal vessel, TAG distal ) where the vessel cross-sectional area fell <2.0 mm 2 .…”
Section: Transluminal Attenuation Gradientmentioning
confidence: 99%